Multiple order-preserving hash functions for load balancing in P2P networks. (2018) - Antoine, Maeva; Huet, Fabrice
Hash functions are at the heart of data insertion and retrieval in DHT-based overlays. However, a standard hash function destroys the natural ordering of data. To perform efficient range queries processing, more and more systems opt for an order-preserving hash function to place data. Unlike a standard hash function, this technique cannot evenly distribute data among peers. We propose a novel approach to improve the data dissemination using several order-preserving hash functions. We describe a protocol that allows an overloaded peer to change its hash function at runtime. Then, we show that all peers should not necessarily use the same hash function in an overlay to insert or look for an item. Finally, we demonstrate through simulations that this strategy greatly improves the dissemination of data items. To our knowledge, this is the first load balancing solution using multiple order-preserving hash functions in structured overlays.